Absorbance analysis of Fe3O4 particles of different scales in silicone rubber at Ku band - Xinhua Song; Xiaojie Li; Honghao Yan (Results in Physics, 2019)
In this paper, the theoretical calculation and experimental study on the absorption characteristics of the (micron and Nano) Fe3O4 particle and silicone rubber hybrid absorber at Ku band (12–18 GHz) are carried out. The absorption curves of Fe3O4 particles with different sizes randomly distributed in silicone rubber are obtained. The results show that the impedance matching characteristics and absorbing effect of nano-Fe3O4 particle and silicone rubber hybrid absorber are better than that of micro-Fe3O4 particle and silicone rubber hybrid absorber. The experimental results show that the attenuation value increases with the increase of frequency, and the attenuation value of nano-Fe3O4 particles and silicone rubber mixed absorber is larger than that of micro-Fe3O4 particles and silicone rubber mixed absorber. The calculated values are in general agreement with the experimental measurements. This study provides a theoretical reference for the practical application of composite absorbing materials (Nano and micro) Fe3O4 particles combined with silicone rubber substrates. Keywords: Ferroferric oxide (Fe3O4), Mixed absorber, Different scales, Absorbance analysis